Clinicopathologic Features in a TSH Secreting Pituitary Tumor : a Case Report - Bakhtiar, Yuriz; Kesumayadi, Irfan; Fujio, Shingo; Arifin, Muhamad Thohar (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Thyrotropin-stimulating hormone-producing adenoma (TSHoma) is a rare cause of hyperthyroidism. Patients with this condition are often diagnosed when the tumor has already grown significantly, as the diagnosis of TSHoma is frequently delayed and confused with primary hyperthyroidism. Our case describes a 60-year-old woman with a goiter who was referred to our center from the otolaryngology department. Her thyroid panel in endocrinology showed elevated free hormone levels (fT3: 4.6 mg/ml and fT4: 1.93 mg/ml) and an unsuppressed TSH: 12.85 μ mIU/l, suggesting central hyperthyroidism. A thyroid gland sample obtained by a fine needle aspiration biopsy did not show malignant cells. An MRI scan of the pituitary gland revealed a macroadenoma with KNOSP grade 1. She underwent transsphenoidal surgery for the tumor. Histopathology revealed an acidophilic adenoma with the expression of TSH and prolactin by immunostaining. The proliferation rate, as indicated by MIB-1 staining, was only 0.6%. The decrease in thyroid hormones after the operation confirmed the effectiveness of the surgery. In conclusion, TSHoma, a rare tumor associated with hyperthyroidism, requires a careful diagnosis for effective management. Our article serves as reference material for understanding cases of pituitary-secreting tumors in Indonesia.